Long-term fertilization and intensive cropping enhance carbon and nitrogen accumulated in soil clay-sized particles of red soil in South China - Xu, Hu; Liu, Kailou; Zhang, Wenju; Rui, Yichao; Zhang, Jingye; Wu, Lei; Colinet, Gilles; Huang, Qinghai; Chen, Xianni; Xu, Minggang (Journal of soils and sediments, 2020)
Purpose Understanding the underlying mechanism of soil carbon (C) and nitrogen (N) accumulation is of great significance for soil C sequestration and climate change mitigation, as well as soil fertility improvement. The objective of this study was to evaluate the response of C and N accumulation in aggregates and fine soil particles to long-term mineral fertilizer and manure application. Materials and methods Five treatments from a long-term experiment with double maize cropping were examined in this study, i.e., (1) no fertilizer (control); (2) mineral nitrogen, phosphorus, and potassium application (NPK); (3) doubled application rate of the NPK (2NPK); (4) pig manure alone (M); and (5) mineral NPK fertilizers and manure combination (NPKM). By using physical particle-sized fractionation, we analyzed soil organic carbon (OC) and total nitrogen (N), and δ 13 C of OC in bulk soil and aggregates (53–2000 μm) and, coarse silt-sized fraction (5–53 μm), fine silt-sized fraction (2–5 μm), and clay-sized fraction (< 2 μm) under those five treatments. Results and discussion Fertilizer application for 24 years, particularly M and NPKM treatments, significantly increased the concentration and proportion of OC and total N associated with aggregates and clay-sized fraction as compared with control. Manure application significantly increased the proportion of OC by 6.6–7.8 points in aggregates, whereas it was by 22.6–25.0 points in clay-sized fraction. Clay-sized fraction-associated C and N showed a non-linear response to C and N accumulation in bulk soil, contributing approximately 47% and 69% to soil OC and total N, respectively. Moreover, the mass proportion of aggregates and the mass ratio of aggregates to fine soil particles increased significantly with C accumulation in fine silt-sized and clay-sized fraction. Conclusions Organic carbon and total nitrogen accumulation in soil clay-sized particles play important role in soil C and N sequestration in red soil. Our results also suggested that C accumulation in fine soil particles might benefit soil aggregation in intensive cropping system of South China.